The Development of E-Module for Batik Local Content in Pekalongan Elementary School - Fisnani, Yeni; Utanto, Yuli; Ahmadi, Farid (Innovative Journal of Curriculum and Educational Technology, 2020)
The teaching materials are to help the teachers in conducting learning activities in the classroom. The materials are written and unwritten. This study purposed to analyze the teaching material using e-module as local content Batik, develop e-module local content Batik that is practically and effectiveness in improving the local content learning for elementary school in Pekalongan, analyze the validity test of Batik’s e-module is to measure the learning of local content for elementary school in Pekalongan, the effectiveness of Batik’s e-module can enhance the learning of local content for elementary school in Pekalongan. This study uses research and development models (R&D). The development of teaching material in this study is Batik’s e-module. The teaching material provides Figures and videos about Batik, so it will be easily for students in understanding the material. The result of the feasibility material by the experts have obtained the percentage 88.6%. Then, the result of media validation is 97.14%. Based on the results validation show that the developing e-module is in the excellent categories, so it has been feasible to be applied in the learning process. The effectiveness tests are conducted in three requirements, there are analyzing the minimum completeness test, individual classical completeness test, and improved learning outcomes. The results of three requirements test, show that Batik’s e-module could improve the students learning outcomes significantly compared to the learning by using the published book. This study is supported in education, to develop Batik’s e-module. The product becomes an alternative media to assist the students learn Batik by using technology. It can also use as a source of reading in the learning of local content.